Estimation of Power/Energy Losses in Electric Distribution Systems based on an Efficient Method - Gheorghe Grigoras; V. Alexandrescu; G. Cartina; Florina Scarlatache (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Estimation of the power/energy losses constitutes an important tool for an efficient planning and operation of electric distribution systems, especially in a free energy market environment. For further development of plans of energy loss reduction and for determination of the implementation priorities of different measures and investment projects, analysis of the nature and reasons of losses in the system and in its different parts is needed. In the paper, an efficient method concerning the power flow problem of medium voltage distribution networks, under condition of lack of information about the nodal loads, is presented. Using this method it can obtain the power/energy losses in power transformers and the lines. The test results, obtained for a 20 kV real distribution network from Romania, confirmed the validity of the proposed method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.2889